2001
DOI: 10.1007/s005350170084
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of serum markers of connective tissue turnover for predicting histological staging and grading in patients with chronic hepatitis C

Abstract: These serum fibrotic markers, especially the serum HA test, would be clinically useful for assessing staging and grading in patients with chronic hepatitis C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(48 citation statements)
references
References 23 publications
(21 reference statements)
3
43
0
2
Order By: Relevance
“…Studies have demonstrated that HA levels correlate with the degree of hepatic fibrosis in patients with chronic HCV. 39,83,84 In alcoholic liver disease, the levels of HA correlate with both the degree of fibrosis and the severity of inflammation. 85 There is a direct linear relationship between HA and procollagen type III amino-terminal peptide (PIIINP) with similar performance by both tests in discriminating between alcoholic patients with and without liver fibrosis.…”
Section: Hamentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have demonstrated that HA levels correlate with the degree of hepatic fibrosis in patients with chronic HCV. 39,83,84 In alcoholic liver disease, the levels of HA correlate with both the degree of fibrosis and the severity of inflammation. 85 There is a direct linear relationship between HA and procollagen type III amino-terminal peptide (PIIINP) with similar performance by both tests in discriminating between alcoholic patients with and without liver fibrosis.…”
Section: Hamentioning
confidence: 99%
“…Studies examining the correlation of MMP-2 in chronic HCV have yielded conflicting results. 38,84,105,106 Little is known about the role of MMP-3 (stromelysin) in liver injury. However, it would appear that levels are of little diagnostic value.…”
Section: Matrix Metalloproteinases and Tissue Inhibitors Of Metalloprmentioning
confidence: 99%
“…Many individual biomarkers have been related to significant fibrosis in CHC patients. These include inflammatory response modifiers such as α2-macroglobulin and haptoglobin [2,3], liver products such as apolipoprotein A1 [3], actual fibrosis components such as hyaluronate and procollagen peptides [4][5][6][7], and matrix proteins such as metalloproteinases and their inhibitors [8][9][10]. It is known that the simultaneous measurement of several biomarkers (the "multibiomarker" approach) could enhance risk stratification.…”
Section: Introductionmentioning
confidence: 99%
“…A biopsia hepática, a ultrassonografia (US) e, mais recentemente, marcadores biológicos e a elastografia transhepática (FibroScan ® ) vêm sendo utilizados para mensurar a fibrose que se desenvolve nas doenças crônicas do fígado (8,15,20,22) . Na EM, a biopsia hepática em cunha, realizada a céu aberto, é o método mais acurado para a mensuração da fibrose periportal, mas implica na realização de laparotomia.…”
Section: Introductionunclassified
“…Além das proteínas responsáveis pela fibrogênese, outras provenientes do processo de degradação da matriz extracelular, também vêm sendo utilizadas na avaliação da fibrose hepática, incluindo o ácido hialurônico, a laminina, o colágeno tipo IV, a hidroxiprolina urinária, entre outras (2,10,11,15,20,22,29) .…”
Section: Introductionunclassified